Two large reciprocal translocations characterized in the disease resistance-rich burmannica genetic group of Musa acuminata - Dupouy, M.; Baurens, F.C.; Derouault, P.; Hervouet, C.; Cardi, C.; Cruaud, C.; Istace, B.; Labadie, K.; Guiougou, C.; Toubi, L.; Salmon, F.; Mournet, P.; et al. (Oxford University Press, 2019)
Banana cultivars are derived from hybridizations involving Musa acuminata subspecies. The latter diverged following geographical isolation in distinct South-east Asian continental regions and islands. Observation of chromosome pairing irregularities in meiosis of hybrids between these subspecies suggested the presence of large chromosomal structural variations. The aim of this study was to characterize such rearrangements.